2012
DOI: 10.1111/j.1476-5381.2011.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

OX1 orexin/hypocretin receptor activation of phospholipase D

Abstract: BACKGROUND AND PURPOSEOrexin receptors potently signal to lipid messenger systems, and our previous studies have suggested that PLD would be one of these. We thus wanted to verify this by direct measurements and clarify the molecular mechanism of the coupling. EXPERIMENTAL APPROACHOrexin receptor-mediated PLD activation was investigated in CHO cells stably expressing human OX1 orexin receptors using KEY RESULTSOrexin stimulation strongly increased PLD activity -even more so than the phorbol ester TPA (12-O-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 79 publications
2
44
0
Order By: Relevance
“…1), but the enzymes responsible for this could not be resolved because of the low selectivity of the inhibitors available (Turunen et al, 2010a). We showed that OX 1 receptors also potently activate both phospholipase C (PLC) and phospholipase D (PLD) cascades (Johansson et al, 2008;Jä ntti et al, 2012), producing diacylglycerol (DAG) and phosphatidic acid (PA), respectively. Both of these compounds could act as substrates for AA release, through the DAG lipase (DAGL)-monoacylglycerol lipase (MAGL) and PA-PLA 2 cascades, respectively, and PA can also be hydrolyzed to DAG by PA phosphohydrolase (reviewed in Kukkonen, 2011).…”
Section: Orexin Receptor Stimulation Induces [mentioning
confidence: 99%
See 2 more Smart Citations
“…1), but the enzymes responsible for this could not be resolved because of the low selectivity of the inhibitors available (Turunen et al, 2010a). We showed that OX 1 receptors also potently activate both phospholipase C (PLC) and phospholipase D (PLD) cascades (Johansson et al, 2008;Jä ntti et al, 2012), producing diacylglycerol (DAG) and phosphatidic acid (PA), respectively. Both of these compounds could act as substrates for AA release, through the DAG lipase (DAGL)-monoacylglycerol lipase (MAGL) and PA-PLA 2 cascades, respectively, and PA can also be hydrolyzed to DAG by PA phosphohydrolase (reviewed in Kukkonen, 2011).…”
Section: Orexin Receptor Stimulation Induces [mentioning
confidence: 99%
“…The average retardation factor values for AA and 2-AG were 0.58 Ϯ 0.01 and 0.67 Ϯ 0.01, respectively. TLC data were quantitated both through imaging plate analysis and through scraping and scintillation counting; the two methods yielded comparable results (Jä ntti et al, 2012). For this reason, only the results from the imaging plate analysis are presented.…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…After thawing, cell debris was spun down and the PLC Activity. Total inositol phosphate release was measured essentially as described in Jäntti et al (2012). CHO-hCB 1 cells were transiently transfected with either OX 1 or M 1 cDNA and also the other vectors included in the Elk-1 luciferase assay in the same ratios to make the assays comparable.…”
Section: Methodsmentioning
confidence: 99%
“…8 A recent study on Chinese hamster ovarian cell lines has revealed other signaling mechanisms like activation of phospholipase D and release of arachidonic acid upon activation of OX 1 orexin receptors. 9 Orexins being excitatory neuropeptides, stimulation of their receptors lead to depolarization by the following mechanisms; (i) activation of NSCC (non -selective cation channels), (ii) stimulation of NCX (sodium calcium exchanger) and (iii) inhibition of potassium channels which are active at rest. 10 Although their signaling mechanisms have been elucidated, their physiological significance still remains elusive.…”
Section: Orexin Signaling Mechanismsmentioning
confidence: 99%